2023
DOI: 10.1126/sciadv.ade2828
|View full text |Cite
|
Sign up to set email alerts
|

A conditional Smg6 mutant mouse model reveals circadian clock regulation through the nonsense-mediated mRNA decay pathway

Abstract: Nonsense-mediated messenger RNA (mRNA) decay (NMD) has been intensively studied as a surveillance pathway that degrades erroneous transcripts arising from mutations or RNA processing errors. While additional roles in physiological control of mRNA stability have emerged, possible functions in mammalian physiology in vivo remain unclear. Here, we created a conditional mouse allele that allows converting the NMD effector nuclease SMG6 from wild-type to nuclease domain-mutant protein. We find that NMD down-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 74 publications
(127 reference statements)
0
25
0
Order By: Relevance
“…FMRP acts as an NMD repressor in neural cells and in its absence, NMD is hyperactivated, leading to widespread transcriptome changes which contributes to intellectual disability and autism (Kurosaki et al, 2021). Recently, a conditional Smg6 mutant mouse model revealed that the NMD pathway has a role in controlling circadian clock regulation (Katsioudi et al, 2023).…”
Section: Nmd Regulationmentioning
confidence: 99%
“…FMRP acts as an NMD repressor in neural cells and in its absence, NMD is hyperactivated, leading to widespread transcriptome changes which contributes to intellectual disability and autism (Kurosaki et al, 2021). Recently, a conditional Smg6 mutant mouse model revealed that the NMD pathway has a role in controlling circadian clock regulation (Katsioudi et al, 2023).…”
Section: Nmd Regulationmentioning
confidence: 99%
“…(D) Expression plots for around-the-clock RNA-seq data from [29] for Tfrc showing mRNA (top panel; exonic reads) and pre-mRNA (bottom panel; intronic reads) for Smg6 mutants (yellow) and controls (blue). RPKM values (reads per kilobase of transcript per million mapped reads) of individual mouse livers are shown as dots with solid lines connecting the means across time points.…”
Section: Resultsmentioning
confidence: 99%
“…The other analysed dataset (Fig. 2D) contained a matching cohort of animals that expressed a catalytically inactive, mutant version of the endonuclease SMG6; this enzyme degrades transcripts targeted through the nonsense-mediated decay (NMD) pathway [29]. Interestingly, at all timepoints Tfrc mRNA abundances were post-transcriptionally increased in Smg6 mutant livers, leading to >2-fold higher mRNA levels; still, mutants showed similar rhythmicity dynamics and peak-to-trough amplitudes in the range of ca.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations